(untitled) (Raparin Journal of Humanities (RJH), 2026)
This study is a part of a scientific investigation into the philosophy of “social change” in the view of Ibn Khaldun. It is divided into three parts, each addressing key topics. The first part searches the concept of “social change”, focusing on Ibn Khaldun’s definition and interpretation. It assesses his analysis of the two different stages of urbanization ”before and after” and shows the signs and characteristics of each stage, connecting them to the broader process of social change. The paper also mentions the effect of geography on behavioral differences and evolving social norms and roles, as discovered through Khaldun’s philosophical views. Furthermore , it examines Ibn Khaldun’s theory on the biological cycle of civilizations, states, and political institutions. The study further highlights the causes and behaviors he identifies as mechanisms driving what he terms "social change," concluding with several essential results and suggestions.